2020
DOI: 10.3389/fpls.2019.01737
|View full text |Cite
|
Sign up to set email alerts
|

An ETHYLENE INSENSITIVE3-LIKE1 Protein Directly Targets the GEG Promoter and Mediates Ethylene-Induced Ray Petal Elongation in Gerbera hybrida

Abstract: Petal morphogenesis has a profound influence on the quality of ornamental flowers. Most current research on petal development focuses on the early developmental stage, and little is known about the late developmental stage. Previously, it was reported that the GEG gene [a gerbera homolog of the gibberellin-stimulated transcript 1 (GAST1) from tomato] negatively regulates ray petal growth during the late stage of development by inhibiting longitudinal cell expansion. To explore the molecular mechanisms of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…The expression of the GASA gene family was strongly inhibited or induced by gibberellin (Figure 7). It has been reported that the GASA gene family was involved in seed germination, shoot and stem elongation, lateral root formation, flowering and flower development, fruit development, and ripening [15][16][17][18][19][21][22][23][24][25]28]. PeuGASAs were also induced or inhibited by EBR, ABA, SA, and MeJA, indicating that GASAs might be extensively involved in the complex plant hormonal signal transduction network [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the GASA gene family was strongly inhibited or induced by gibberellin (Figure 7). It has been reported that the GASA gene family was involved in seed germination, shoot and stem elongation, lateral root formation, flowering and flower development, fruit development, and ripening [15][16][17][18][19][21][22][23][24][25]28]. PeuGASAs were also induced or inhibited by EBR, ABA, SA, and MeJA, indicating that GASAs might be extensively involved in the complex plant hormonal signal transduction network [26].…”
Section: Discussionmentioning
confidence: 99%
“…AtGASA5 delayed flowering time by enhancing the expression of FLC and repressing the expression of FT and LEAFY [17]. GhGEG, a gene from the GASA gene family in Gerbera hybrida, was directly transcriptional activated by GhMIF and GhEIL1 to inhibit the ray petal elongation and cell elongation during petal development [21,22]. AtGASA4 regulated the differentiation and development of flower development meristem and increases the seed size and yield of Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…GAs are among the universal plant phytohormones that play a crucial role in the growth and development processes, including germination, stem elongation, photosynthesis, flowering, and seed development, while GASA -like genes possess a key role in GAs signaling pathway [ 12 , 22 , 23 ] in different plants viz. gerbera [ 24 ], and maize [ 10 ]. Some GASA genes are regulated by other hormones, as RSI1 was regulated by IAA [ 25 ], and OsGSR1/2 was regulated by GA3 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional analysis of GhCYC proteins revealed redundant functions of GhCYC2, GhCYC3 and GhCYC4 in regulating ray floret identity and in promoting petal development ( Juntheikki-Palovaara et al, 2014 ). Various hormones (gibberellin, abscisic acid, ethylene, and BRs) are involved in the regulation of late-stage petal development in gerbera ( Zhang et al, 2012 ; Li et al, 2015 ; Han et al, 2017 ; Huang et al, 2017 , 2020 ; Ren et al, 2018 ). Li et al (2015) found that GA 3 stimulates petal elongation in gerbera, while ABA inhibits it.…”
Section: Introductionmentioning
confidence: 99%